ANALISIS SUPERVISI AKADEMIK KEPALA SEKOLAH UNTUK MENINGKATKAN KINERJA GURU DI SMP NEGERI 13 BINJAI - Amini Amini; Mega Pati Aritonang; Indra Prasetia (Universitas Negeri Medan, 2021)
This study aims to determine and analyze in depth the performance of academic supervision carried out by school principals in improving teacher performance at SMP N 13 Binjai. The research method uses qualitative data collection techniques, observations, interviews and conclusions. The results of the study show that in planning for academic supervision, information is obtained that principals always give authority to teachers in appreciating their innovations in teaching. The principal also made a visit to the teacher's room. The point is to directly check the state of teacher development in preparing administration. Supervision of the implementation of supervision by the principal in this covid situation uses the sigum application where with this application teachers will be given the convenience of uploading data and increasing the use of science and technology. Supervision activities that will be carried out by the school principal are well prepared. The implementation of academic supervision by the principal does not reduce the principal's assessment as a supervisory supervisor to assist teachers in improving teacher performance. Coaching and training is one of the forms provided by the principal which is the embodiment not to judge teachers but rather to direct the skills of teachers to be more able to innovate. Preparation of the syllabus, prota, prosem, lesson plans to the preparation of effective teaching hours. In addition, the principal provides direction to teachers in the form of motivation to teachers, where this is able to provide encouragement to develop teacher performance in their respective competencies. The role of the principal to provide input, ideas or forms of reprimand is a good attitude to achieve educational progress at SMP N 13 Binjai. Academic supervision that has been carried out by the principal has gone through many stages, such as direct coaching with face-to-face and online (in a network). The principal also provides more maximum direction at the end of the evaluation. Because there will be deficiencies in the learning process. These deficiencies are used to process and analyze the evaluation results. Based on the results of interviews and observations that provide guidance on learning evaluation as a form of follow-up. This guidance is direct by the supervisor and principal at the time the evaluation takes place. If the principal and the supervisory team find teachers who have difficulties in carrying out learning evaluations, the team will try to overcome them.